Determinan Partisipasi Masyarakat dalam Program Keluarga Berencana (KB) di Kecamatan Denpasar Selatan Kota Denpasar - Dewanta, Kadek Raditya; Yasa, I Nyoman Mahaendra (Innovative: Journal Of Social Science Research, 2024)
This research analyzes the influence of education level, age, family income and government intervention on community participation in the family planning program in South Denpasar District in 2022. The main aim of this research is to analyze the influence of education level, age, family income and government intervention simultaneously and partially as well as analyzing government intervention in moderating the level of education on community participation in family planning programs in South Denpasar District. The data used in this research is primary data, namely by conducting structured interviews with respondents. The research population was all couples of childbearing age who participated in the family planning program in South Denpasar District, totaling 19,412 people. The sampling method used was purposive sampling. In this research, the number of samples determined to be studied was 100 women with married status who participated in an active family planning program using the Moderated Regression Analysis technique. Based on the analysis, the results showed that education level, age, family income and government intervention simultaneously had a significant effect on community participation in family planning programs. Education level, age, family income and government intervention partially have a positive and significant effect on community participation in the family planning program in South Denpasar District. Government intervention partially moderates the positive influence of education level on community participation in family planning programs in South Denpasar District. The results of this research have the implication that government intervention is an important indicator in increasing community participation in family planning programs. Effective government intervention can influence and moderate the relationship between other factors, such as education level, age, and family income, on community participation in family planning programs. The need for strong government support, sustainable policies, and adequate resource allocation to facilitate and increase community participation in family planning programs.